Fostering Empathy, Unravelling Privilege and Ability: Films as a Pedagogic Tool in Initial Teacher Preparation - Sharma, Smriti (Voices of Teachers and Teacher Educators, 2023)
The theoretical frame of the paper is situated in the works of Paulo Freire, Pierre Bourdieu and Carl Rogers. The conceptual frame ‘Socially Just Teacher Education’ is rooted in the understanding and recognition of education and schooling as a site of philosophical, ideological and pedagogical struggle. The aim of teacher preparation then is to prepare teachers to be aware of the inequalities existent in the society while also empowering the prospective teachers to challenge these. Given this, the current research was undertaken as an action research whose aim was to use films to sensitise the student-teachers about the existent inequalities and make them critically reflect on those. The methodological frame of the research is qualitative. the data collection as well as the analysis of data were iterative processes done through open coding followed by theoretical coding. The emerging themes of the analysis are- ’Drawing out of social mutism’, Unravelling privilege and ability through critical and liberating dialogue’, ’Making it alive: Using films to evoke emotive responses’ The research highlights the possibilities of preparing reflective practitioners through use of critical pedagogy of films.